Peningkatan Mutu Prestasi & Minat Bakat SMTPI Jemaat Bethesda melalui aplikasi Microsoft Power Point - Joanna Cristy Patty; Dennis Rian Lopulissa; Imanuel Lorenzo Pattiasina (Universitas Lancang Kuning, 2021)
Education accompanied by creativity is an inseparable part. Through education and creativity, it is hoped that it can change the mindset of humans to be wider and have quality behavior. In addition, education is also often referred to as the process of educating. The educational process is generally carried out in schools, institutes, academies, high schools, universities and so on. The development of Information and Communication Technology is currently experiencing very rapid changes and developments. Many new innovations in various fields have begun to be developed and involved in technological incubators such as business, industry, agriculture, health, and without exception education in particular, in providing learning process media. The world of education is also accompanied by the importance of creativity from students, so the author feels to increase student creativity with Power Point training as a form of creative presentation in schools whose activities are carried out at SMTPI Bethesda.